The Clinical Manifestation Variety and Management Choice of Meckel’s Diverticulum with Complication: A Single Center Experience - Tingliang Fu; Xiaoliang Xu; Lei Geng; Yanli Huang; Guojian Ding; Hong Ji (Gastroenterology Research and Practice)
Background. The study was to analyze the clinical manifestation variety and management choices of symptomatic Meckel’s diverticulum in children. Methods. From July 2008 to October 2018, 28 cases of Meckel’s diverticulum with a variety of complications were admitted to our hospital. The clinical data included age, gender, symptoms and signs, investigations, intraoperative and pathological findings, and outcome. Results. The ratio of males to females was 2.5 : 1. The diagnoses were made by 99mTc-pertechnetate scan (in 5 cases) and by exploratory laparotomy (in 2 cases). The initial diagnosis in the other cases includes intussusception (in 4 cases), acute appendicitis (in 5 cases), intestinal obstruction (unknown origin), peritonitis, and even shock in 12 cases. Laparoscopic surgery was performed in 8 cases; 18 cases underwent open surgery. Excision of partial bowel segment with diverticulum and primary anastomosis was done in 22 cases and wedge resection of diverticulum in 4 cases. Two other cases received nonoperative therapy and went to other hospitals to receive surgical management. Ectopic gastric mucosa in the diverticulum was found in 9 cases, including 6 cases with lower gastrointestinal bleeding. Conclusion. The clinical characteristics of Meckel’s diverticulum varied. Children with hematochezia, peritonitis, and intestinal obstruction without history of prior abdominal operation should be suspected with this disease until proven otherwise. Hematochezia is often associated with ectopic gastric mucosa in the diverticulum. Laparoscopic surgery should be one of the choices for the diagnosis and treatment of Meckel’s diverticulum with complications.